Case Study-Based Learning Media Innovation Integrated With Lumi Education to Improve Student Critical Thinking - Rizka, Mifta; Permatasari, Silvia; Arianto, Jumili; Alia Sari, Filma; Ryantama Isjoni, M. Yogi; Sahara (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
The development of technology has triggered various innovations in the world of education, especially in learning media which plays an important role. With the increasing need for digital-based learning to support distance learning, the development of digital technology-based learning media is very important. In addition, case study-based learning is an important aspect in improving students' critical thinking skills. To answer these challenges, Lumi Education integrated case study-based learning media was designed. This research aims to develop learning media based on case studies integrated with Lumi Education to improve students' critical thinking skills. This research was conducted at the Faculty of Teacher Training and Education. Riau University. This research procedure follows the 4-D development model. However, it only reaches the development stage, which includes three stages: Define, Design and Develop.Defining stage includes analyzing needs, developing case concepts, designing case structures and determining supporting materials, Second, the Design Stage which includes making materials, designing learning media based on case studies and media validation by experts. From the results of media validation by media validator material validators, the case study-based learning media integrated with Lumi Education is categorized as feasible and can be applied in the lecture process. This development produces practical and high-quality media products that aim to improve students' critical thinking skills.